SCIENTIFIC RESEARCH AND SUSTAINABLE DEVELOPMENT IN AMAZONIA - Alberto Capiberibe, João; Cabral de Castro, Manoel; Ruellan, Alain (Science & Technology Journals, 2005)
In Amazonia, sustainable development requires the dispersed occupation of the ecosystems by human populations living principally from these enhanced resources: it is human presence, living in harmony with the environment, that can save Amazonia. The strategy calls for promoting specific and diversified human occupations that permit the sustainable nondestructive use of the enormous and complex diversity of Amazonia’s wealth and functions. Success requires the discovery of new knowledge and the making of social and technological choices. Scientific and technological research must now define its priorities in relation to these needs and choices: the research must be multi- and inter-disciplinary, rooted in Amazonia itself, working in close contact with the population concerned, and taking the time to discover and use their knowledge.